A educação superior privada e o curso bacharelado de administração: estudo de uma IES privada de Maceió - Gonçalves, Sandra de Lourdes (2012)
The study aims to find out how the actors of the course Bachelor of Directors ( teachers , managers and coordinator ) , a private institution understand the factors that modify the way to see the educational function and how this education makes sense only integrated transformation of society. Neves (2004 ) states that urban intellectuals in the strict sense are formed , increasingly , schools of higher education, with his training directed to the scientific and technological knowledge necessary for the reproduction of capital , strengthening the relationships between education and production and thus to understand if the actors of private higher education ( teacher , coordinator and managers ) are aware of how educational policies implemented since 1990 have interfered in higher education , and to what extent this interference affects the activities performed by these actors . The study has as starting point to carry out exploratory and descriptive research , and analyzed the contemporary state in which it discusses the recent transformations of capitalism , seeking to exploit a line featuring contemporary capitalism , the analysis of the interviews , aims to reveal the vision of the management of the Bachelor in Management of Private HEIs studied , and thus envision new perspectives for studies , considering that the studies conducted show a more complex reality , which foster new needs reflection. As for the fact that private institutions have to function to integrate the teaching to the productive sector , training the workforce , ie the preparation of the individual for economic and productive processes , at different levels of complexity . Finally , the analysis of the research and the theoretical framework leads to the conclusion that the expansion of higher education strengthens the guideline to certify skilled labor to perform complex tasks in the job market .